2017
DOI: 10.1002/asna.201713300
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of helicity oscillations in the saturation of the Tayler instability

Abstract: Recent numerical results of current-driven instabilities at low magnetic Prandtl number and high Hartmann number support the possibility of a saturation state characterized by helicity oscillations. We investigate the underlying mechanism by analyzing this possibility using a higher order Landau-Ginzburg effective Lagrangian for the weakly nonlinear amplitude dynamics, where the magnetic and velocity perturbations are linearly dependent. We find that, if the mirror symmetry between left-and right-handed modes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The observed helicity oscillation seems to be a generic feature of the saturated TI for large enough Ha at low Pm (note that Bonanno and Guarnieri [14] could not find helicity oscillations in a dissipation-free model). We ask now for its possible implications for Tayler-Spruit type stellar dynamos.…”
Section: Synchronized Helicity Oscillations and The Solar Dynamo Cyclementioning
confidence: 85%
“…The observed helicity oscillation seems to be a generic feature of the saturated TI for large enough Ha at low Pm (note that Bonanno and Guarnieri [14] could not find helicity oscillations in a dissipation-free model). We ask now for its possible implications for Tayler-Spruit type stellar dynamos.…”
Section: Synchronized Helicity Oscillations and The Solar Dynamo Cyclementioning
confidence: 85%
“…Beyond flux-tube approximation, the existence of any TI-related α-effect is still a matter of debate. Various authors (Chatterjee et al, 2011;Gellert, Rüdiger, and Hollerbach, 2011;Bonanno et al, 2012Bonanno et al, , 2017 had evidenced spontaneous symmetry breaking between left-and right-handed TI modes, leading indeed to a finite value of α, but mainly for comparably large values of the magnetic Prandtl number [P m], i.e., the ratio between viscosity and magnetic diffusivity. Things are different, though, for the case of low P m, as it is typical for the solar tachocline region where P m is believed to lie in the range 10 −3 ...10 −2 .…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of such a TI-related α effect is far from trivial, though. For comparable large values of the magnetic Prandtl number [P m], Chatterjee et al (2011);Gellert, Rüdiger, and Hollerbach (2011); Bonanno et al (2012Bonanno et al ( , 2017 found evidence for spontaneous symmetry breaking between left-and righthanded TI modes, leading indeed to a finite value of α. Things are different, however, for low P m (as typical for the solar tachocline) for which we observed a tendency of the TI to produce oscillations of the helicity and the α-effect related to it (Weber et al, 2013(Weber et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%